Hydrogen-Bonded Ladder Motifs in Naphthalene Dicarboxamides: Influence of Linear vs. Angular Amide Orientation - Abdulrahman Mohabbat; István Boldog; Takin Haj Hassani Sohi; Nils Reistel; Philipp Seiffert; Christoph Janiak (Crystals)
The crystal structures of naphthalene dicarboxamides, namely 1,4-naphthalene dicarboxamide (1,4-NDA), 2,6-naphthalene dicarboxamide (2,6-NDA), and 2,7-naphthalene dicarboxamide (2,7-NDA), are presented for the first time, along with an analysis of their supramolecular organization. The compounds, obtained in single-crystalline form via solvothermal crystallization from methanol, are stable in air to near 350 °C and have melting points above 300 °C. In their densely packed structures (ρ = 1.43–1.47 cm3g−1) the combination of <semantics><msubsup>C11</msubsup></semantics> (4) chains and <semantics><msubsup>R22</msubsup></semantics>(8) rings generates one-dimensional hydrogen-bonded ladders, with an additional <semantics><msubsup>R42</msubsup></semantics>(8) pattern. The amide groups and the naphthalene rings form dihedral angles between 22° and 40°. Neighboring H-bond ladders run parallel in 1,4-NDA and 2,6-NDA and are connected by means of the naphthalenedyil cores so that two-dimensional (2D) H-bonded sheets are obtained. Except for a weak intra-sheet π–π stacking in 1,4-NDA, there are no π–π stacking and C–H⋯π interactions. The <semantics><msubsup>R22</msubsup></semantics>(8) rings act as four-connected nodes, leading to the formation of two-dimensional H-bonded planar sheets with sql topology for the nearly linear dicarboxamides 1,4-NDA and 2,6-NDA and cds topology for the angular 2,7-NDA. Hirshfeld surface analysis and NCI plots provide additional insight into the H-bonding interactions.